2019
DOI: 10.1021/acs.molpharmaceut.9b00157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Melanin Characteristics on Drug Binding Properties

Abstract: Melanins are biopolymers encompassing a high degree of chemical heterogeneity. Binding of small-molecule drugs to ocular melanin significantly affects the ocular pharmacokinetics, and could serve as a strategy for prolonged drug retention in the eye. The influence of the structural and physical characteristics of melanins originating from different sources on their drug binding properties has not yet been methodically investigated. We performed physical characterization of Sepia officinalis, synthetic and porc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Overall, the preparation of melanin nanoparticles was crucial for the use of MST, because aggregation and adsorption were seen with unmodified synthetic and isolated melanin (porcine RPE [ 9 ]; data not shown). Furthermore, the previous work of Jakubiak et al [ 36 ] showed correlation among the drug binding to different melanin types (porcine RPE-choroid, sepia, and synthetic), supporting the notion that melanin binding is a robust phenomenon over melanin from different sources.…”
Section: Discussionsupporting
confidence: 66%
“…Overall, the preparation of melanin nanoparticles was crucial for the use of MST, because aggregation and adsorption were seen with unmodified synthetic and isolated melanin (porcine RPE [ 9 ]; data not shown). Furthermore, the previous work of Jakubiak et al [ 36 ] showed correlation among the drug binding to different melanin types (porcine RPE-choroid, sepia, and synthetic), supporting the notion that melanin binding is a robust phenomenon over melanin from different sources.…”
Section: Discussionsupporting
confidence: 66%
“…Similar to its ability to bind ions, melanin is known to bind and accumulate drugs within its structure, with this property known since at least the 1960s. For examples, see references [39,[114][115][116][117][118][119][120].…”
Section: Unique Physico-chemical Propertiesmentioning
confidence: 99%
“…Melanin is a negatively charged biopolymer that colors various human structures such as skin, hair, and eyes [ 38 ]. The main biological function of melanin is to exert a cytoprotective effect against noxious UV radiations by serving as a physical barrier and absorbent filter that reduces their penetration through the epidermis [ 39 ], as well as against oxidative stress damage by scavenging free radicals [ 40 ]. Hence, melanin can bind small molecules, leading to their retention in the pigmented tissues [ 40 ] followed by a slow release of the accumulated toxins [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main biological function of melanin is to exert a cytoprotective effect against noxious UV radiations by serving as a physical barrier and absorbent filter that reduces their penetration through the epidermis [ 39 ], as well as against oxidative stress damage by scavenging free radicals [ 40 ]. Hence, melanin can bind small molecules, leading to their retention in the pigmented tissues [ 40 ] followed by a slow release of the accumulated toxins [ 37 ]. In particular, melanin interacts by hydrogen and π−π bonding with small aromatic molecules [ 40 ] such as RUT.…”
Section: Discussionmentioning
confidence: 99%